Dysembryoplastic neuroepithelial tumours - Noman Ahmed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2025)
Dysembryoblastic neuroepithelial tumour (DNET) arerare, benign WHO grade I glioneuronal tumours thatmainly affect children and adolescents, commonlypresenting with drug-resistant seizures. They typicallyarise in the temporal lobe cortex and show characteristicMRI features of cortical based, multicystic lesions withoutsignificant oedema or mass effect. Histologically, DNETshave a multinodular architecture with glioneuronalcomponents and are classified into simple, complex, andnonspecific subtypes. Gross total resection is thetreatment of choice, offering excellent seizure control andprognosis, while incomplete resection increases the riskof recurrence. Though malignant transformation isuncommon, reported cases highlight the importance oflong-term follow-up. Early diagnosis, complete excision,and sustained surveillance are essential to achievingfavourable outcomes. Keywords: Dysembryoblastic neuroepithelial tumour(DNET), Seizures, Outcomes